Integrating modern biotechnology into agricultural improvement in Africa - International Livestock Research Institute (International Livestock Research Institute, 2012)
Speaking at the launch of the Biosciences eastern and central Africa-International Livestock Research Institute (BecA-ILRI) Hub on 5 November 2010, Prof. Aggrey Ambali, Director - Policy Alignment and Programme Development Directorate and Advisor - New Partnership for Africa's Development (NEPAD) Science and Technology reflects on the importance of research to address problems of hunger, low agricultural productivity, rapid population growth and natural and human made disasters.